CONTRIBUCION AL CONOCIMIENTO DE LOS NEMATODOS DE LAS AVES DE MEXICO V - CABALLERO Y C, EDUARDO; C, EDUARDO (My University, 1839)
A monographic account, with descr of Oxyspirura crassa* from Bubo virginianus melancerus, and Aprocta travassosi* from Curucujus massena
MEM SOC CIE ANTONIO ALZATE
Keywords: CONTRIBUCION, CONOCIMIENTO, NEMATODOS, AVES DE MEXICO V; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL